Jobs with equality - Kenworthy, Lane (New York, 2008)
"Economic and social shifts have led to rising income inequality in the world's affluent countries. This is worrisome for reasons of fairness and because inequality has adverse effects on other socioeconomic goods. Redistribution can help, but government revenues are threatened by globalization and population aging. A way out of this impasse is for countries to increase their employment rate. Increasing employment enlarges the tax base, allowing tax revenues to rise without an increase in tax rates; it also reduces welfare state costs by decreasing the amount of government benefits going to individuals and households. The question is: Can egalitarian institutions and policies be coupled with employment growth? For two decades conventional wisdom has held that the answer is no.